Development of application method for fabricating functionally graded adhesive joints by two-component acrylic adhesives with different elastic moduli. Issue 5 (1st June 2019) - Nakanouchi, M.; Sato, C.; Sekiguchi, Y.; Haraga, K.; Uno, H.
ABSTRACT: A method for fabricating adhesively bonded joints with graded properties along the bond-line was proposed. By utilizing two types of acrylic adhesives, one hard and the other soft, the properties of the mixture were changed by controlling the mixing ratio. An applicator for the adhesives was developed and used for the experiments, in which property-graded adhesive layers were actually produced. The properties, i.e., stress-strain curves at various points of the property-graded adhesive layer, were experimentally measured, and the validity of the proposed method was confirmed. The Young's moduli at multiple points of the adhesive layer changed from 34.7 MPa to 634 MPa by changing the mixing ratio of the adhesives.